Attribution and scarcity analysis of blue and green water resources in a river basin under climate and environmental change - Yang Liu; Zhaoyang Zeng; Chengguang Lai; Sijing He; Jie Jiang; Zhaoli Wang (Ecological Indicators)
Water resources are pivotal for sustaining human development. Understanding the variations and driving mechanisms of blue and green water resources is essential for the effective management and planning of regional water resources. Based on land use and land cover (LULC) data from 1980, 2000, and 2015, three SWAT models were developed for the Hanjiang River Basin (HRB), and five simulation scenarios were designed to estimate the spatiotemporal evolution, driving factors, and scarcity of blue water (BW) and green water (GW). The results indicate that BW is more abundant in the northern HRB, while GW is more concentrated in the south. The green water coefficient ranges from 0.39 to 0.60. In HRB, climate change is the primary driver of variations in BW and GW, with relative contributions of 72.03–79.49% and 50.79–52.25%, respectively. Among different LULC types, forest and cropland are significant drivers of both BW and GW changes. The contribution of urban land is higher in the second period (2000–2015) than in the first period (1975–2000). BW is strongly driven by precipitation and negatively affected by potential evapotranspiration (PET), while GW is primarily influenced by PET. From 2003 to 2016, the HRB experienced moderate blue water scarcity (average of 1.16) and moderate green water scarcity (average of 0.70). The Falkenmark Index for the HRB ranges from 500 to 1700, with an average of 1126.21, indicating prevailing water stress and water scarcity. Both blue and green water scarcity are mainly affected by precipitation, PET, and the normalized difference vegetation index (NDVI); PET exacerbates both, while precipitation and NDVI mitigate them. This study jointly assessed the attribution and scarcity of BW and GW and further analyzed the individual impacts of multiple climatic and LULC factors, offering a more nuanced perspective compared to previous studies. The findings provide a scientific basis for regional water resource management, agricultural water use optimization, and enhancement of ecosystem resilience under changing climate and land use conditions.